Representasi Eksploitasi Perempuan dalam Iklan - Wicaksono, Ignatius Prasetyo (FISIP Universitas Atma Jaya Yogyakarta, 2012)
Abstract: Exploitation representation is how meaning is produced, exchanged, represented and exploited for the benefit of users. Exploitation of women means utilizing all the things that are attached to women, both images and signs attached to them. Exploitation of women represented in the advertisement as part of the appeal of sales message. In the version of Berrygood advertisement Ã¢â‚¬Å“Bikin Good MoodÃ¢â‚¬Â is the ad that represents subliminal exploitation of women. This article discusses how the basic structure of the narrative in the advertisement, represent the exploitation of women through feminist Marxist perspective. The method of analysis used is Greimassian semiotic analysis using two stages.Abstrak: Representasi eksploitasi adalah bagaimana makna diproduksi, dipertukarkan, diwakilkan dan dimanfaatkan demi kepentingan pengguna. Eksploitasi pada perempuan berarti pemanfaatkan segala hal yang melekat pada perempuan, baik citra maupun tanda yang melekat kepadanya. Eksploitasi perempuan direpresentasikan dalam iklan sebagai bagian dari daya tarik pesan penjualan. Iklan Berrygood versi Ã¢â‚¬ÂBikin Good MoodÃ¢â‚¬Â adalah iklan yang merepresentasikan eksploitasi perempuan secara subliminal. Artikel ini mendiskusikan bagaimana struktur dasar narasi dalam iklan tersebut merepresentasikan eksploitasi perempuan melalui sudut pandang Feminis Marxis. Metode analisis yang digunakan adalah analisis semiotika Greimassian dengan menggunakan dua tahap.